2022
DOI: 10.3390/plants11081086
|View full text |Cite
|
Sign up to set email alerts
|

Growth Characteristics of Chlorella sorokiniana in a Photobioreactor during the Utilization of Different Forms of Nitrogen at Various Temperatures

Abstract: The cultivation of microalgae requires the selection of optimal parameters. In this work, the effect of various forms of nitrogen on the growth and productivity of Chlorella sorokiniana AM-02 when cultivated at different temperatures was evaluated. Regardless of the temperature conditions, the highest specific growth rate of 1.26 day−1 was observed in modified Bold’s basal medium (BBM) with NH4+ as a nitrogen source, while the highest specific growth rate in BBM with NO3− as a nitrogen source achieved only 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 56 publications
1
10
0
1
Order By: Relevance
“…Thus, biomethane released from anaerobic reactors can be further used for the local production of heat and electricity [ 4 ]. In addition, CO 2 from biogas and nutrients from digestate can be used to produce algal biomass [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, biomethane released from anaerobic reactors can be further used for the local production of heat and electricity [ 4 ]. In addition, CO 2 from biogas and nutrients from digestate can be used to produce algal biomass [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Изготовители продуктов питания, кормов, косметики, товаров для здоровья, также заинтересованы в повышении продуктивности C. Vulgaris [1]. Промышленные предприятия, культивирующие C. vulgaris в крупных масштабах, испытывают потребность в эффективных способах усиления роста и продуктивности C. Vulgaris [14,47,49].…”
Section: зеленая одноклеточная водоросльunclassified
“…Chlorella can use ammonium for growth, making it possible to use this alga for bioremediation to remove ammonium [75]. Ziganshina et al reported that the highest growth rate (1.26/day) was observed in modified Bold's basal medium (BBM) with ammonium, while the growth rate in BBM with nitrate was only 1.07/day [76]. Thus, although Chlorella strains seem tolerant to ammonium, the degree of growth inhibition by ammonium varies between the strains [71,77,78].…”
Section: Ammoniummentioning
confidence: 99%